At the crossroads between autonomy and vulnerability: where we are and where we want to go (De Legibus - Law Journal, 2024)
The aim of this study is to highlight and emphasize reflections on family mediation as an alternative method for resolving disputes involving elderly individuals. Considering the unique characteristics of conflicts among family members during this phase of life, it is crucial to promote and establish family mediation as the preferred method for resolving disputes involving the elderly and their families. Furthermore, we intend to explore the need to create new legal instruments within our legal framework that enable asset protection and the provision of care to vulnerable adults through private autonomy and self-regulation. In this regard, it is important to assess the feasibility of establishing the codification in our Civil Code of a contract aimed at providing care, as well, a functionalized patrimonial estate in favor of the vulnerable person.
Keywords: Elderly; Vulnerability; Autonomy; Family Mediation; Caregiving; Asset Protection